Superior mesenteric artery pseudoaneurysm rupture: a rare complication of pancreatic surgery - Semião,Carolina (2021)
Abstract Pseudoaneurysms after gastro-intestinal tract surgery are rare. Most of them occur after biliary tract and pancreatic surgery. They can lead to potentially serious consequences, such as rupture, hemorrhage and death. For these reasons, pseudoaneurysms should be diagnosed and treated as soon as possible.